Immigrant investors in financial markets: modes of financial behavior - Kushnirovich, Nonna (Journal of Business Economics and Management, 2016)
This study investigates the modes of financial behavior of immigrants, comparing them with native-born investors. The study developed a theoretical framework for investigating the determinants of financial behavior, combining Bourdieu’s concept of economic habitus with the theories explaining behavior of investors in financial markets. Methods of clustering analysis and multinomial logit regression model were used. The study found that an investor’s behavior mode is strongly predicted by determinants derived from cultural, economic and social capital. For low-income persons, the culture of origin shapes their financial behavior, and for high-income persons, their economic capital and affiliation to social class are more important. Over time, immigrants assimilate in their financial choices. This study contributes to research of financial behavior as well as migration research by explaining the factors that affect preferences for financial assets allocation among immigrants. Understanding migrants’ modes of financial behavior will help policymakers to facilitate accumulation of wealth by immigrants, and in this way contribute to the process of their integration.